Consideration of gravity as a possible etiological factor in amyotrophic lateral sclerosis. (November 2019) - Akaishi, Tetsuya; Takahashi, Toshiyuki; Abe, Michiaki; Aoki, Masashi; Ishii, Tadashi
Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease with an unknown mechanism of onset that predominantly impairs the upper and lower motor neurons. Components of the sensory and autonomic nervous system were once thought to be spared in the disease, but more recently they have been identified to be impaired at various levels. However, some of the motor neurons such as oculomotor, abducens, or pudendal nerves are spared even in the later stages of ALS. The mechanism of such complex and heterogeneous neuronal loss in typical ALS is still unknown. In this study, the characteristics of the nervous system involved in the pathogenesis of ALS were comprehensively reviewed. As a result, the direction of the axon in the anatomical position, rather than the functional type or length of the axon, was suggested to contribute the most to the onset of ALS. This finding suggested that downward directed axons, represented by motor neurons, require extra energy to move waste or unnecessary substances from the synapse side to the neural cell body with retrograde fast axonal transport. Based on this theory, the extra energy that is required in vertically directed axons due to the effect of gravity was mathematically estimated. As a result, several percent more adenosine triphosphate molecules were suggested to be consumed in vertical axonal transport by gravity, compared to those consumed in transverse axonal transport. Because most of the motor neurons project downward in the anatomical position, unretrieved waste will gradually sediment in axon terminals by gravity, which could eventually result in motor neuron-dominant neuronal loss. Although the theory that gravity is one of the mechanisms responsible for ALS is still hypothetical, it is theoretically reasonable and compatible with the clinical manifestations of the disease. Further basic research studies with cultured neurons or animal models are necessary to confirm the association between gravity and the onset of ALS.